(untitled) (Italian Journal of Public Health, 2007)
Health Technology Assessment (HTA) can represent an innovative and effective approach to supply decisionmakers with a valid instrument to improve the allocation of resources in the field of vaccines. We proposed a HTA approach for considering the introduction of a new vaccine that could potentially have a great impact on the population’s health, using as an example the vaccine against Human Papilloma Virus (HPV). This approach could be of great interest when the decision making process involves choices regarding new vaccines. We developed a HTA approach for assessing all of the aspects involved in the introduction of vaccines against HPV in Italy, considering the following issues: - epidemiological evaluation of HPV infection and related pathologies through the consultation of data banks and the scientific literature; - evaluation of health care resources utilisation by people suffering from the infection/ related diseases, through the consultation of hospital archives; - systematic review and meta-analysis of randomised clinical trials on HPV vaccination effectiveness and safety; - mathematical modelling and economic evaluation of the vaccination using a cost-effectiveness analysis; - evaluation of the impact of vaccination on the Health System [organisational aspects, vaccine surveillance, relationship between different decisional levels (national, regional)]; - analysis of the ethical, social (acceptability, availability, accessibility, information) and legislative aspects of vaccination. A HTA report on the new vaccine could represent an new important tool to support the choice of decision makers in order to better inform the allocation of economic resources and maximize healthcare services, since it takes into account not only the burden and the epidemiology of the disease, and the economic evaluation of different scenarios, but also the social, legal and bioethical aspects. For HTA to support the introduction of new technologies, and new vaccines can be considered in this sense, there to utilise a process that is well defined, transparent and widely used.